Efektifitas Virgin Coconut Oil VCO dengan Lotion dalam Pencegahan Dekubitus pada Pasien Imobilisasi - Betty Sunaryanti; Ratna Kusuma Astuti (Mathematics Education Study Program, 2025)
Immobilized patients are more prone to pressure ulcers, bedsores or decubitus ulcers. The aim of this study was to determine the effectiveness of using coconut oil with lotion in preventing decubitus in immobilized patients. This type of research is an experiment with a quasi-experimental design. The population is patients who are at risk of developing pressure sores in the Inpatient Ward of RSUD Dr. Moewardi Surakarta. The sampling technique was consecutive sampling, so that using the experimental group (pure coconut oil) 12 patients with 2 reserve patients and the control group (lotion) 12 patients with 2 reserve patients, the number of sample members was 28 patients. The data analysis technique uses a t-test at a significance level of 95%. The results showed that almost half of the VCO (39.3%) used had no signs and symptoms of pressure sores, while the use of a small portion of lotion (17.9%) did not find any signs and symptoms of pressure sores. Pure coconut oil is effective in preventing decubitus for immobilized patients.